The Role of Educational Administration in Digital Literacy Development: Transformative Strategies for Enhancing 21st Century Competencies - Irmawanti Tahir; Anne Abdul Rachman (International Journal of Educational Development, 2025)
The digital era has revolutionized educational systems, making digital literacy a vital competency for the 21st century. As such, educational administration plays a pivotal role in driving digital transformation within schools. This study used a qualitative approach with a multi-case study design, examining 20 secondary schools to assess how effective educational administration practices contribute to the sustainable implementation of digital literacy programs. Data were gathered through in-depth interviews with 60 educational administrators, participant observations, and the analysis of policy documents. The findings reveal that educational administration, when proactive, collaborative, and data-driven, significantly boosts student digital literacy. In fact, schools employing these practices experienced an improvement in digital literacy by up to 65% within two years of program implementation. The success of these programs was largely attributed to key factors such as visionary leadership, strategic allocation of resources, continuous teacher capacity development, and robust monitoring systems. Additionally, the research highlights the importance of a comprehensive approach to digital literacy, where educational leaders understand the interconnections between various administrative functions and their impact on digital education. This includes integrating strategic planning, operational execution, developmental efforts, evaluation processes, and collaborative work between teachers and administrators. In response to these findings, the study proposes the Integrated Digital Literacy Administration Model (MALDT). This model offers a framework that can be adapted by educational institutions to enhance learning quality in the digital age. It emphasizes the need for a holistic approach to digital literacy administration, combining leadership vision with operational efficiency and continuous professional development. Ultimately, the adoption of such a model can help schools foster an environment where digital literacy is embedded into the core educational experience, ensuring students are adequately prepared for the challenges of the digital era.